The Kargil Conflict: A case of Civil Military-Split - Butt, Saima (Annals of Human and Social Sciences, 2023)
The Kargil conflict was a small-scale war between India and Pakistan that lasted from May to July 1999 in the Kargil district of Kashmir along the line of control. The goal of this study was to better comprehend the international and national pressures on Pakistan as a result of the Kargil conflict. The fight began when Pakistani forces took the high mountain peaks of the Kargil sector, which the Indian army had left owing to harsh winter weather. This essay explores what were the reasons behind Pakistan's backing for the Kargil conflict. The fight lasted two months, and both sides incurred significant casualties. To support the argument, data were obtained from primary and secondary sources, and the research type is descriptive and historic.